Critical effect of the N2 amino group on structure, dynamics, and elasticity of DNA polypurine tracts - Lankas, Filip; Cheatham, Thomas E; Spacková, Nad'a; Hobza, Pavel; Langowski, Jörg; Sponer, Jirí (Biophysical journal, 2002)
Unrestrained 5-20-ns explicit-solvent molecular dynamics simulations using the Cornell et al. force field have been carried out for d[GCG(N)11GCG]2 (N, purine base) considering guanine*cytosine (G*C), adenine*thymine (A*T), inosine*5-methyl-cytosine (I*mC), and 2-amino-adenine*thymine (D*T) basepairs. The simulations unambiguously show that the structure and elasticity of N-tracts is primarily determined by the presence of the amino group in the minor groove. Simulated A-, I-, and AI-tracts show almost identical structures, with high propeller twist and minor groove narrowing. G- and D-tracts have small propeller twisting and are partly shifted toward the A-form. The elastic properties also differ between the two groups. The sequence-dependent electrostatic component of base stacking seems to play a minor role. Our conclusions are entirely consistent with available experimental data. Nevertheless, the propeller twist and helical twist in the simulated A-tract appear to be underestimated compared to crystallographic studies. To obtain further insight into the possible force field deficiencies, additional multiple simulations have been made for d(A)10, systematically comparing four major force fields currently used in DNA simulations and utilizing B and A-DNA forms as the starting structure. This comparison shows that the conclusions of the present work are not influenced by the force field choice.
Keywords: Purines; molekulární modely; polydeoxyribonukleotidy; DNA; pružnost; Elasticity; Models, Molecular; konformace nukleové kyseliny; Nucleic Acid Conformation; puriny; párování bází; vodíková vazba; Polydeoxyribonucleotides; Hydrogen Bonding; Base Pairing